From hospital to post-acute care organizations: the relationship between patient experience and health recovery - Nascimento, G.; Nunes, F. G.; Anderson J. (International Journal of Quality in Healthcare, 2020)
Objective: To determine to what extent patient health status and recovery in post-acute care organizations (PACO) is related to patient experience of the discharge process from hospital and to patient experience while staying in these facilities. Design: Longitudinal study of patients discharged from hospitals to post-acute care organizations. Setting: 12 hospitals and 14 PACO Portuguese organizations. Participants: 181 patients participated in the both stages of data gathering. Main Outcome Measures: Patients’ physical and mental health status was measured through the SF-36 scale. The experience of transition from hospital to post-acute care organizations was measured with the Care Transition Measure. The Picker Adult In-Patient Questionnaire was used to measure patients’ experience in these organizations. Results: Patients reporting better physical condition in post-acute care organizations had a better experience on discharge [b = 0.21, 95% CI (0.10, 0.31)] and perceive fewer problems inside facilities [b = -0.19, 95% CI (-0.31, 0.08)]. The experience in post-acute care organizations is significantly related to patients’ mental health status [b = -0.47, 95% CI (-0.59, -0.36)]. Patients showing higher levels of physical recovery had a better experience on discharge [b = -0.18, 95% CI (0.08, 0.28)], while those registering better mental recovery experienced fewer problems during their stay [b = -0.41, 95% CI (-0.52, -0.30)]. Conclusions: PACO play a key role in maintaining and promoting patients’ health and this goal is influenced by their experience both in the transition from hospitals to PACO and while staying in these facilities.